(untitled) (Research, Society and Development, 2025)
Diabetes mellitus is a chronic and progressive endocrinopathy commonly observed in small animals, with a multifactorial etiology and diverse clinical manifestations. In dogs, the most prevalent form is type 1 diabetes, characterized by autoimmune destruction of pancreatic beta cells, whereas in cats type 2 diabetes predominates, associated with insulin resistance and often linked to obesity. The presente work aimed to carry out a literature review on diabetes mellitus in cats and dogs, adressing its clinical and pathophysiological forms, risk factors, clinical signs, diagnosis, treatment and complications based on recent scientific evidence. A literature review was conducted based on books and scientific articles published between 2007 and 2025, obtained from PubMed, Scopus, ScienceDirect, and Google Scholar, using inclusion criteria that ensured the relevance and up-to-date nature of the information. The studies indicate common clinical signs such as polyuria, polydipsia, polyphagia, and weight loss, as well as complications including cataracts in dogs, neuropathy in cats, and diabetic ketoacidosis. Diagnosis is based on the persistent presence of hyperglycemia and glycosuria, supported by laboratory tests. Treatment involves appropriate insulin therapy, individualized nutritional management, and effective home care. It is concluded that therapeutic success depends on early diagnosis, an understanding of species-specific pathophysiology, and the owner’s commitment to clinical follow-up and glycemic monitoring, promoting the animal’s quality of life.